DECODING CULTURAL NUANCES: SUBTITLING CULTURAL TERMS IN NETFLIX ORIGINAL SERIES “GADIS KRETEK” - Anggia Yanuar Prasastri; Ina Sukaesih (Politeknik Negeri Jakarta, 2024)
Audiovisual translation, particularly subtitling, plays a crucial role in bridging cultural gaps for a global audience by making local expressions and culturally-bound references accessible across languages. The globalization of media content has increased the demand for accurate and culturally sensitive subtitles, prompting a deeper examination of how cultural nuances are conveyed in translation. This study investigates the translation of cultural terms in the Netflix Original Series Gadis Kretek. The objectives are to (1) classify cultural terms based on Newmark's (2017) framework, (2) analyze the subtitling strategies used, following Pedersen's (2011) theory, and (3) evaluate translation accuracy using Nababan et al.'s (2012) criteria. Employing a descriptive qualitative method and Spradley's (1980) analytical approach, 206 data of cultural terms were identified. Social Culture was the most common category, comprising 136 data (66.01%), followed by Material Culture (21.85%), Organization (8.25%), and Ecology (3.89%). This study found six subtitling strategies: retention, specification, direct translation, generalization, substitution, and omission. Direct translation was the most frequently used strategy (61.65%), while specification was the least used (1.46%). Translation accuracy was assessed through a Focus Group Discussion (FGD), which showed that strategies such as Direct Translation and Retention achieved higher accuracy by preserving cultural context. Conversely, Generalization and Omission often resulted in lower accuracy due to a loss of cultural specificity. Overall, the translation quality of cultural terms in Gadis Kretek was rated as accurate, with an average score of 2.93.